Infestations Of Two Major Pests Of Cocoa, Conopomorpha Cramerella and Helopeltis Theivora Under Natural Condition - Saripah binti Bakar (Indonesian Coffee and Cocoa Research Institute, 2019)
The Cocoa pod borer (CPB), Conopomorpha cramerella (Snellen) (Lepidoptera: Gracillariidae) and Helopeltis theivora (Miller) (Hemiptera: Miridae) are the major pests of cocoa in the South East Asian Region. C. cramerella started to infest cocoa pod which more than 7cm in length, whereas H. theivora started to infest the pod at a very early stage of pod development. The present study aims to determine the relationship and the degree of damage severity of these two significant pests under natural condition. No insecticide spraying was carried out throughout sampling occasions; however, other management practices were implemented. Destructive sampling of fifty cocoa pods at various lengths was carried out at fortnightly basis.Percentage of infestation, number of CPB eggs, entry, and exit holes were recorded for an individual pod. The results obtained denoted that H. theivora begin attacking pods at a young age and the majority of the pods were infested when they reached 8 cm in length. The percentage of damage severity increased as the pod developed. In contrast to H. theivora incidence, the number of C. cramerella eggs were recorded higher when the percentage of H. theivora incidences were low. The highest mean number of C. cramerella eggs were recorded when the pod length is more than 150 mm. Although infestation of the C. cramerella was more serious, management of both pests must be started when the pod length is less than 8 cm. Integrated control approaches must be targeted to both pests at the appropriate time, to reduce significant losses.